Chromium and its role in the human body including the antidiabetic action - Pierzak, Monika (Journal of Education, Health and Sport, 2018)
Chromium is an element belonging to micronutrients, which is about 0.012% of the coating earth. Chrome Latin language. chromium was discovered in 1798 by the French researcher Louis Nicolas Vauquelin in the periodic table element belongs to the group VI A transition having an atomic number of 24 and an atomic weight of 51.996, chrome "Chroma" in Greek means "color". It owes its name to chemical compounds, which element is formed on all oxidation; +1 to + 6 [4,7,8]. Chromium is an element which, in the environment occurs in two forms as Cr (III) and Cr (VI) [4,5,6,8]. The role of the element in the human body primarily is seen in the metabolism of carbohydrates, proteins, lipids, and especially cholesterol levels [1]. Chromium as a chemical compound in the oxidation of Cr (III) is part of enzymes, ribonucleic acids, accelerates blood coagulation and also increases the activity of B-glucuronidase. The properties element plays a key role in the antioxidant during the synthesis of RNA and DNA immune response affects the synthesis of certain vitamins and hormones. In adult women for the correct standard daily intake of chromium with the diet I recognize the value of 25 µg in men 35 µg [7,8].Keywords: chrome, diabetes, cardiovascular disease, hypoglycemia, supplementation